Telecommunications, Transportation and Location (Edward Elgar, 2006)
This book looks at the economics of the evolving interface between the movement of people, goods and information (telecommunications). It illustrates the increasing importance of information flows in relation to how people move about, the ways that goods are transported and on land-use patterns. The authors show how the linkages involved are not static but vary as technology develops, as social priorities shift, and as policymakers adjust institutional structures. The situation is evolving but, nevertheless, from a public policy and a narrower commercial, business perspective, it is important to gain broad insights into what is occurring and the ways that telecommunications, transportation, and location interact. This is the focus of the book.